Building a resilient organization through a pre-shock strategic emphasis on innovation - Andreas Engelen; Constantin Huesker; Verena Rieger; Victoria Berg (Journal of Product Innovation Management, 2023)
Why are some firms more resilient when systemic shocks like the Global Financial Crisis (GFC) or COVID-19 pandemic set in? We approach this question by arguing that a firm's pre-shock strategic emphasis on innovation can mitigate the consequences of such shocks by facilitating stability and flexibility, major components of organizational resilience, as the shock sets in. We test our arguments empirically by analyzing data from 2003 to 2011 on as many as 994 firms from the S&P 1500 to identify the causes of their resilience during the 2008 GFC. Our findings indicate that pre-shock product introductions and, to some extent, top management's focus on innovation can facilitate stability and flexibility when a shock occurs, while R&D intensity and patents, other dimensions of a strategic emphasis on innovation, do so only when firm profitability before the shock is low. In this way, we direct innovation research's attention to the additional performance benefits of innovation activities when shocks occur and reveal which dimensions of a strategic emphasis on innovation buffer the negative consequences of a shock, thus providing insights into how innovation helps firms be resilient. Further, our theorizing and empirical findings unveil an intriguing paradox: While existing research tends to find positive associations between innovation and profitability in “regular” times, strong pre-shock profitability impairs innovation's ability to unfold its effects fully at shock onset.
Keywords: 650; new product introductions; organizational resilience in times of crisis; patents; R&D intensity; top management focus on innovation